The complete mitochondrial genome of an agama, Phrynocephalus putjatia (Reptilia, Squamata, Agamidae). (3rd March 2016) - Tong, Haojie; Jin, Yuanting
Abstract: The complete mitochondrial genome was sequenced from the toad-headed viviparous lizard, Phrynocephalus putjatia . The mitogenome was 16, 283 bp in length; it contained 13 protein coding, 22 tRNA, 2 rRNA genes and 2 control regions. The gene order and compositions were identical with all published congeneric mitogenomes for the fragment between 12 s RNA and tRNA-Thr, but with some differences for the remaining sequences including CR, tRNA-Pro and tRNA-Phe . The characteristics of the mitogenome was analyzed and discussed in detail.